Reduced cannibalistic behavior of African catfish, clarias gariepinus, larvae under dark and dim conditions - Mukai, Yukinori; Sanudin, Noorsyarinah; Firdaus, Rian Freddie; Saad, Shahbudin (Zoological Society of Japan, 2013)
In general, African catfish shows higher survival rates in the dark conditions than in the light conditions. In this study, larval behavior of African catfish was observed under 0, 0.01, 0.1, 1, 10, and 100 lx using a CCD camera to investigate the reason why African catfish larvae show higher survival rates in dark conditions. The larvae showed significantly higher swimming activity under 0, 0.01, and 0.1 lx than that under 10 and 100 lx. The larvae also showed significantly increased aggressive behavior under 10 and 100 lx; the swimming larvae attacked resting individuals more frequently under 10 and 100 lx than under 0, 0.01, and 0.1 lx. The aggressive behavior and sharp teeth of the attacking larvae appeared to induce skin surface lesions on injured larvae. Chemical substances were then generated from the injured skin surface, and these chemical stimuli triggered cannibalistic behavior in other fish near the injured fish. The results of this study demonstrate that the higher survival rates of African catfish larvae under dark conditions are a result of inactivity and subsequent increase in chemical releasing stimuli concentrations around inactive individuals that triggers feeding behavior in nearby active catfish. Therefore, we recommend larval rearing of African catfish in dark or dim conditions, as it improves catfish survival rates.